The religion clauses : the case for separating church and state - Chemerinsky, Erwin; Gillman, Howard (New York, NY : Oxford University Press, 2020)
In 'The Religion Clauses', Erwin Chemerinsky and Howard Gillman examine the extremely controversial issue of the relationship between religion and government. They argue for a separation of church and state. To the greatest extent possible, the government should remain secular. At the same, time they contend that religion should not provide a basis for an exemptions from general laws, such as those prohibiting discrimination or requiring the provision of services.
Also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on July 22, 2020).
Keywords: Church and state -- United States; Religion and state -- United States; Freedom of religion -- United States; Law; Laws of specific jurisdictions & specific areas of law